The necropolitical crisis of racial subjectivity in the South African postcolony: black consciousness as a technology of the self and the limits to transformation - Naicker, Veeran (Department of Sociology, 2022)
In this thesis, I problematize whether Steve Biko's Black Consciousness Philosophy, reread as an affective and psychic Foucauldian technology of the self can operate as a strategy of psychic repair and transformation for pathological racialised subjects, produced by Necropolitical governmentality in the South African colony and postcolony. Centrally, I argue that Foucault's revolutionary reading of ancient Greek notions of parrhesia and political spirituality can be found in Biko's work on Black Theology and the reconstruction of Black subjectivity through several rational techniques that are performatively embodied in his writings and sacrificial militancy, deploying death as politicizing mechanism via the figure-Frank Talk. The pathologies of the South African postcolony are bequeathed to us via the Atlantic slave trade, colonial and Apartheid governance, engendering intergenerational traumas that have been institutionalised, internalised, and inverted in contemporary postcolonial discourses on African selfhood with detrimental and precarious consequences for political minorities and women. Although I interrogate anticolonial scholarship from a predominantly postcolonial perspective which includes a diagnosis of African political subjectivity in the Black Radical Tradition, the theoretical toolbox that animates my analysis is drawn from a post-structural combination of Michel Foucault's work on governmentality as a combination of technologies, that is, political rationalities of domination or social subjugation and technologies of the self, Jacques Derrida's deconstruction, and several strands of psychoanalysis. Deploying Foucault's toolbox enables me to articulate a historical and nominalist account of African state formations without a relation to a general Weberian model, Marxist political economy, specifically the historical constitution of the body as labour power and psychoanalysis, particularly the desiring subject. Through this approach, I aim to undermine the universality of Eurocentric and essentialist conceptions of modern subjectivity as epistemic or discursive constructs that have become points of identification in symbolic systems. However, I argue that despite being valuable for understanding contemporary Europe, Foucault's conception of biopolitics cannot account for the reciprocal constitution of modernity, colonialism, and capitalism in the rest of world. Therefore, I have employed Achille Mbembe's notion of Necropolitics to account for contemporary, violent death practices in the governance of colony and postcolony, as well as the global precarity that results from the age of the Anthropocene and the becoming black of the world, signalling the limits of Biko's Africanist humanism, metaphysics (Ubuntu) and the racial animus of his followers in the contemporary context.